2016
DOI: 10.1111/1475-6773.12505
|View full text |Cite
|
Sign up to set email alerts
|

Priorities for Patient‐Centered Outcomes Research: The Views of Minority and Underserved Communities

Abstract: Members of underserved communities, in informed deliberations, prioritized research on Quality of Life, Patient-Doctor, Special Needs, Access, and Compare Approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…A description of Tier 1 deliberative engagement activities in ‘health ecosystem priority setting’ were limited to Khodyakov’s [ 13 ] literature review, and were limited in description. The literature better emphasized highly-structured patient and public engagement planning processes and activities for research, including the James Lind Alliance Priority Setting Partnerships (UK) [ 10 , 16 , 24 35 ], the Dialogue Method (Netherlands) [ 25 , 36 39 ], Global Evidence Mapping (Australia) [ 5 ], and the Deep Inclusion Method/CHoosing All Together (US) [ 21 , 40 ]. While these research planning processes and activities differed, a common approach across Tier 1 public and patient engagement priority setting in research planning included gathering and analyzing identified research priorities by engaging patients and the public along with clinicians and researchers, followed by prioritization of topics through dialogue between all stakeholders.…”
Section: Resultsmentioning
confidence: 99%
“…A description of Tier 1 deliberative engagement activities in ‘health ecosystem priority setting’ were limited to Khodyakov’s [ 13 ] literature review, and were limited in description. The literature better emphasized highly-structured patient and public engagement planning processes and activities for research, including the James Lind Alliance Priority Setting Partnerships (UK) [ 10 , 16 , 24 35 ], the Dialogue Method (Netherlands) [ 25 , 36 39 ], Global Evidence Mapping (Australia) [ 5 ], and the Deep Inclusion Method/CHoosing All Together (US) [ 21 , 40 ]. While these research planning processes and activities differed, a common approach across Tier 1 public and patient engagement priority setting in research planning included gathering and analyzing identified research priorities by engaging patients and the public along with clinicians and researchers, followed by prioritization of topics through dialogue between all stakeholders.…”
Section: Resultsmentioning
confidence: 99%
“…To adapt CHAT to the unique needs and objectives of research priority setting with minority and underserved communities, we utilized a participatory process, led by a Steering Committee comprised of a † We describe the priorities for health research spending selected by participants using this exercise elsewhere. 35,47…”
Section: Me Thodsmentioning
confidence: 99%
“…Gaining consensus about which research efforts are most likely to advance science, inform best practices to improve the outcomes and experiences of patients and caregivers, and identify gaps in knowledge is central to this goal. Although research priorities have traditionally been set by researchers and clinicians (5), engaging patients and informal family and formal nonfamily caregivers has been found to establish research agendas that are "more just, more accountable, and more responsive to patients' needs and values" (6). The James Lind Alliance's guidelines on the methods of establishing priority setting partnerships (PSPs) have been important in engaging clinicians, policy makers, patients, and caregivers in setting research agendas that accelerate patient-centered research (7,8).…”
Section: Methods Phase 1 Selection and Approval Of Candidate Survey mentioning
confidence: 99%